Connecting landscape-scale ecological restoration and tourism: stakeholder perspectives in the great plains of North America. Issue 11 (19th September 2022) - Clark, Connor; Nyaupane, Gyan P.
Abstract: This grounded theory research seeks to understand stakeholder attitudes towards tourism development and ecological restoration around a landscape-scale ecological restoration project in Montana, USA. Due to the limited number of landscape-scale ecological restoration projects across the globe, research on stakeholder attitudes and the relationship of tourism with such projects is missing. Only recently have researchers begun to take an interest in the relationship between tourism and rewilding, a subfield of ecological restoration that involves the restoration of wildlife. The results derived from interviews with various stakeholder groups, including nonprofit conservation groups, a national wildlife refuge, the local ranching community, a county commission, and local residents working in the tourism industry demonstrate important, emerging themes, such as contrasting worldviews, ecological paradigm, landscape-scale land management, and lack of shared community vision. As local ranchers are particularly threatened by landscape-scale ecological restoration efforts, integrated threat theory is used to describe intergroup conflict in a tourism and ecological context. A revised tourism area life cycle (TALC) model using a tourismscape framework and core-periphery concept is proposed to understand the interrelationships between regional tourism and landscape-scale ecological restoration areas. The importance of bottom-up solutions, community-driven initiatives, and stakeholder engagement in the planning process is emphasized.